Dy3+‐doped Y3Al5O12 transparent ceramic for high efficiency ultraviolet excited single‐phase white‐emitting phosphor. Issue 6 (26th November 2018) - Zheng, Ruilin; Ding, Jianyong; Zhang, Qi; Li, Binbin; Wang, Zhongyue; Liu, Chunxiao; Lv, Peng; Yu, Kehan; Wei, Wei
Abstract: A kind of Dy‐doped yttrium aluminum garnet (YAG) transparent ceramic for ultraviolet excited single‐phase white light‐emitting phosphor was investigated, which has high‐quantum efficiency (45%). The temperature field of Dy:YAG transparent ceramic was calculated by steady‐state thermal simulation. Moreover, by combining with 365 nm light‐emitting diodes (LED) chip directly, the Commission Internationale de l'Éclairage coordinate ( x  = 0.33, y  = 0.35) is close to the standard equal energy white light illumination. The Dy:YAG transparent ceramic, possessing of good optical and thermal properties, is promising for applications in high‐power LEDs devices.